Internalisasi Nilai Antinarkoba Sebagai Mekanisme Sosial: Pendekatan Fungsionalisme Terhadap Sosialisasi BNN Kabupaten Sidoarjo - Irawan, Faiz Muktar Ghonim (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Drug abuse among students has become a serious concern, as they are in a vulnerable phase of identity and value formation. The socialization efforts carried out by the National Narcotics Agency of Sidoarjo Regency (BNNK Sidoarjo) serve as a crucial preventive strategy. This paper aims to describe how the educational content delivered in BNNK Sidoarjo’s outreach programs contributes to the development of anti-drug awareness and social values among students. This study adopts a qualitative descriptive approach, with data collected through direct observation of outreach activities and an analysis of the official presentation material titled Indonesia Darurat Narkoba. The findings show that the outreach materials emphasize values such as responsibility, social awareness, and self-control as foundations for building anti-drug attitudes. The use of interactive delivery methods and narrative-based messages further strengthens students' understanding of drug dangers in everyday life contexts.